Evolutionary relics dominate the small number of secondary metabolism genes in the hemibiotrophic fungus Dothistroma septosporum. Issue 5 (May 2019) - Ozturk, I. Kutay; Dupont, Pierre-Yves; Chettri, Pranav; McDougal, Rebecca; Böhl, Ole J.; Cox, Russell J.; Bradshaw, Rosie E.
Abstract: Fungal secondary metabolites have important functions for the fungi that produce them, such as roles in virulence and competition. The hemibiotrophic pine needle pathogen Dothistroma septosporum has one of the lowest complements of secondary metabolite (SM) backbone genes of plant pathogenic fungi, indicating that this fungus produces a limited range of SMs. Amongst these SMs is dothistromin, a well-characterised polyketide toxin and virulence factor that is required for expansion of disease lesions in Dothistroma needle blight disease. Dothistromin genes are dispersed across six loci on one chromosome, rather than being clustered as for most SM genes. We explored other D. septosporum SM genes to determine if they are associated with gene clusters, and to predict what their likely products and functions might be. Of nine functional SM backbone genes in the D. septosporum genome, only four were expressed under a range of in planta and in culture conditions, one of which was the dothistromin PKS backbone gene. Of the other three expressed genes, gene knockout studies suggested that DsPks1 and DsPks2 are not required for virulence and attempts to determine a functional squalestatin-like SM product for DsPks2 were not successful. However preliminary evidence suggested that DsNps3, the only SM backbone gene to be most highly expressed in the early stage of disease, appears to be a virulence factor. Thus, despite the small number of SM backbone genes in D. septosporum, most of them appear to be poorly expressed or dispensable for virulence in planta . This work contributes to a growing body of evidence that many fungal secondary metabolite gene clusters might be non-functional and may be evolutionary relics. Highlights: Dothistroma septosporum has nine secondary metabolite (SM) backbone genes. Besides the characterised dothistromin gene, only three SM genes were expressed. Preliminary evidence suggests the expressed DsNps3 gene produces a virulence factor. Predicted cyclopiazonic acid and squalestatin metabolites were not detected. Most of these SM genes appeared non-functional or silent under tested conditions.